1997
DOI: 10.1038/42716
|View full text |Cite
|
Sign up to set email alerts
|

A dendritic-cell-derived C–C chemokine that preferentially attracts naive T cells

Abstract: Please be advised that this information was generated on 2018-05-11 and may be subject to change. letters to natureSequences (MIPS) databases were reconciled. Ty elements and dubious open reading frames (ORFs) were excluded. The data set (5,790 proteins) and search results can be viewed at the URL http://acer.gen.tcd.ie/~khwolfe/yeast. Repetitive regions within proteins were masked using the SEG filter in BLAST.Statistical analysis. Chi-square tests (data not shown) indicate that duplicated genes in yeast are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
343
3
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(367 citation statements)
references
References 17 publications
11
343
3
4
Order By: Relevance
“…However, it is becoming increasingly more evident that chemokines play an important role in the migration and recruitment of immune cells including DC and T cells in vivo. 15,16 Lymphotactin (Lptn) is a C chemokine that specifically regulates the migration of T cells and NK cells. [17][18][19][20] Dilloo et al 21 reported that cotransfection of Lptn and interleukin-2 (IL-2) genes into tumor tissue could induce potent antitumor immunity through an attraction-expansion approach.…”
Section: Ance To Tumor Challenge Most Effectively It Was Found That mentioning
confidence: 99%
“…However, it is becoming increasingly more evident that chemokines play an important role in the migration and recruitment of immune cells including DC and T cells in vivo. 15,16 Lymphotactin (Lptn) is a C chemokine that specifically regulates the migration of T cells and NK cells. [17][18][19][20] Dilloo et al 21 reported that cotransfection of Lptn and interleukin-2 (IL-2) genes into tumor tissue could induce potent antitumor immunity through an attraction-expansion approach.…”
Section: Ance To Tumor Challenge Most Effectively It Was Found That mentioning
confidence: 99%
“…This idea is supported by a study that showed a 60-fold increase in DC-CK1 mRNA production in dendritic cells that undergo maturation (21). In addition, DC-CK1 expression has been detected in both germinal centers and T cell areas of lymph nodes, areas where primary B and T cell responses take place (18,20). Furthermore, a recent in vivo study has shown that naive T cells cluster in the vicinity of mononuclear cells, producing DC-CK1 mRNA in portal area lymphoid follicles of livers from patients with chronic hepatitis C (22).…”
mentioning
confidence: 98%
“…In vitro studies have revealed that DC-CK1 induces both intracellular Ca 2ϩ mobilization and chemotaxis in CD4 ϩ and CD8 ϩ T cells bearing the naive T cell marker CD45RA, but not in T cells bearing the activation marker CD45RO and not in nonlymphocytic cells such as monocytes and granulocytes (18,19). Another study revealed that DC-CK1 is also chemotactic for CD38-negative mantle zone B cells, indicating that this chemokine acts not only on naive T cells, but on naive B cells as well (20).…”
mentioning
confidence: 99%
“…Here the DCs are able to activate the specific immune system. [20][21][22] Since 1996, there have been several clinical studies investigating tumor antigen-loaded DC-based vaccines, mainly in metastatic melanoma patients. 23,24 Over the years, many parameters in DC vaccination have been optimized in clinical studies.…”
Section: Introductionmentioning
confidence: 99%